An attractive path to use of green resources for production of antibacterial and antioxidant wool yarns - Somayeh Baseri (Scientific Reports)
Abstract The worldwide agricultural and food industries produce serious environmental pollution problems as well as increased costs of waste disposal. While the agro-food wastes are able to provide valuable resources for the production of bio-materials to promote circularity of the agro-food chain obtaining a better balance between economic, environmental, and social aspects. Today’s society is then becoming more and more sensitive to such important issues as resource optimization and ecologically sound waste management strategies for a sustainable future. Bio-finishing of textile materials emerges as an effective solution to management of agro-food wastes and alleviate environmental pollution. In this way, for the first time, a bio-mordant by-product was recovered from the mango seed kernel to replace metallic mordanting agents in the dyeing process of wool with natural dye extracted from the leaves of S. rebaudiana through the two conventional and ultrasound-assisted procedures. The influence of the main process parameters on the dyeing efficiency was evaluated and an efficient mathematical model was developed to provide the best dyeing conditions at minimum materials and energy costs. Results revealed that while the ultrasound method was able to improve extraction efficiency, the bio-materials produced in this study could further display good antioxidant activity, antibacterial performance, and enhanced color fastness. Moreover, the elaborated dyeing process reduced the environmental parameters (BOD5 and COD). The findings foresee developing a new sustainable process for the resource optimization of mango seed kernel and S. rebaudiana leaves to decrease the agro-food wastes disposal impacts as well as close he loop in the circular bio economy.